Activity Patterns among Young Women: A Time Budget Perspective - Winkler, Renata; Moczulska, Marta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: In this article, our aim is to identify and assess changes in the behaviour of young women taking into account the changes regarding gender and cultural roles.Research Design & Methods: Analysing seven-day diary data (N = 139), we examined the average duration of the 12 evaluated categories of activity and their percentage contribution to the structure of young women’s daily time budget. A hierarchy of women’s activities in each of the five survey editions was established (2018–2022).Findings: By comparing the time budget structures across editions, trends in women’s activity levels, and an existing dependence between specific categories of activity in each edition were identified.Implications / Recommendations: The withdrawal of young women from physical activity (limiting the time they devote to it) may be associated with significant health consequences for them in the future. The confirmed changes in the lifestyle of successive years of young (post-adolescent) women might signal a change in their comprehension of social expectations assigned to the roles fulfilled by women, and thus their level of involvement in support, care, and voluntary activities. Some limitations related to this study were recognised. Female students from a single university were surveyed, so results are not non-generalisable. In terms of place, cultural factors could be taken into account. Therefore, the authors suggest undertaking research among university students in not only in other locations but also in other countries.Contribution: The study reveals trends in young women’s activity levels and an existing dependence between specific categories of their activity.